Pengaruh Motivasi Kerja Dan Pelatihan Kerja Terhadap Kinerja Karyawan Pada CV. Central Rezeki Motor Medan - Robin, Robin; Denni, Denni; Jesica, Jesica (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Employee performance is a benchmark used by the organization in reflecting its success. Employees can be considered successful if they are able to complete the tasks assigned by the organization. However, there are several factors that can affect employee performance which in turn can have a good / bad impact on the organization. one of those factors is motivation and job training. providing motivation to employees is the obligation of the leadership so that employees are able to increase work productivity. Companies usually prepare each employee to get to know their job better and continue to provide learning guidance in the long run. This study aims to determine whether there is an influence between work motivation and job training on employee performance in the management department of the Management study program of the College of Business Management Multi Sarana Management Administration and Engineering Technology (STMB MULTISMART) Medan. The research method used is quantitative research method where the sampling technique used is saturated sampling technique or census. The results showed that motivation is able to contribute to employee performance, meaning that motivation plays an important role in shaping employee productivity. Therefore, employees who have high motivation tend to be more productive towards employee performance. Job training is able to contribute to employee performance where the more job training provided to employees, the higher employee performance, so that with an increase in employee performance it can improve company development.